Quranic Hermeneutics and Sufism of Syaykh Abd al-Qadir al-Jilani - Masduqi, Irwan (Center for Research and Development of Religious Literature and Heritage, 2015)
Syaykh Abdul Qadir al-Jilani is the founder of Tariqah Qadiriyyah. His teaching is highly respected by the leaders of many Islamic traditional boarding schools in Indonesia. They have accepted his teachings from his works entitled Futih al-Gayb, al-Fath al-Rabbani, al-Gunya li Ţalibi Tariq al- Haqq, and Kitāb Sirr al-Asrar wa Mazhār al-Anwar. Then, in 2009, there was a discovery of al-Jilani's commentary of Qur'an entitled al-Fawātiḥ al- Ilahiyyah wa al-Mafatih al-Gaybiyyah al-Muwadihah li al-Kalim al- Qur'aniyyah wa al-Hikam al-Furqaniyyah. As one of teachers traditional Islamic boarding school, I am interested in examining the authenticity of al- Fawatiḥ al-Ilahiyyah wa al-Mafatiḥ al-Gaybiyyah al-Muwadihah li al-Kalim al-Qur'aniyyah wa al-Hikām al-Furqaniyyah. This research also discusses the interpretation of the Al-Qur'an in the view of Shaykh Abd al-Qadir al-Jilani and his methods.